Comparisons of performance indicators between Super Rugby and Currie cup competition during 2014 season - Schoeman, R.; Coetzee, D.; Schall, R. (South African Journal for Research in Sport, Physical Education and Recreation, 2017)
Previous studies on differences in level of competition in rugby focused on physiological and psychological components, yet little research is available on comparing performance indicators between different levels of play. This study attempted to compare performance indicators of Currie Cup and Super Rugby, and to differentiate between the winning and losing teams of both competitions. A total of 30 games played during the 2014 Super Rugby competition and 30 games played during the 2014 Currie Cup were observed. The numbers of most match activities were similar for two competitions, with the average numbers of lineouts, scrums, rucks, tackles and penalties differing by 3% or less between competitions. Statistically and practically significant differences between competitions were for mauls and missed tackles. The average of 6.4 mauls in Super Rugby was significantly lower than the average of 9.6 in the Currie Cup, with a rate ratio of 0.69, implying a difference in the average number of mauls of about 30%. Similarly, the average number of missed tackles was about 20% lower in the Super Rugby competition compared to the Currie Cup. Average numbers of activities were also generally similar for winning and losing teams in the two competitions.